Congress, keystone of the Washington establishment - Fiorina, Morris P. (Yale University Press, 1989)
"This highly readable book makes a strong case that a Washington establishment does exist and that members of Congress are responsible for it. Fiorina's description of the self-serving interconnections that have developed between Congress, bureaucrats, and citizens with special interests leads to provocative and disturbing conclusions about the way our political system works. First published in 1977, this greatly enlarged second edition discusses the new developments that have occurred over the past twelve years, provides supportive data through the 1988 election, and reveals Fiorina's current thoughts on Congress and American politics."--